2014
DOI: 10.1016/j.jnci.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Isolated loco-regional recurrence after radical nephrectomy for renal cell carcinoma: A study of 22patients

Abstract: ILR after radical nephrectomy for RCC is more common with more advanced stages, where interval to recurrence tends to be shorter. The management should be surgical, which was possible in nearly 60% of cases. Complete excision was associated with better overall and disease free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Consistent with previous reports, the median time to development of RFR after RN in the present cohort was 1.4 years. This relatively short median time to development of RFR after RN is consistent with previous studies, in which median time to recurrence ranged from 1.1 to 3.3 years . The majority of these lesions were discovered on standard surveillance imaging.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous reports, the median time to development of RFR after RN in the present cohort was 1.4 years. This relatively short median time to development of RFR after RN is consistent with previous studies, in which median time to recurrence ranged from 1.1 to 3.3 years . The majority of these lesions were discovered on standard surveillance imaging.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, efforts to reduce the incidence of LRR after RN for locally advanced RCC should be made in patients with risk factors, despite distant metastasis being the main pattern of recurrence after RN for locally advanced RCC [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study showed that LRR as the first recurrence event is significantly associated with subsequent distant metastasis or death. Therefore, efforts to reduce the incidence of LRR after RN for locally advanced RCC should be made in patients with risk factors, despite distant metastasis being the main pattern of recurrence after RN for locally advanced RCC [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to different sources, the prevalence of this dangerous occurrence ranges between 2 and 10% [ 7 , 8 ]. The interim between nephrectomy and development of LR is variable – from 3 months to 45 years – which calls attention to the momentousness of long-term follow-up [ 9 ]. What is more important – patients with isolated LR are at higher risk of distant metastatic disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%